MicroRNAs miR-16 and miR-519 control meningioma cell proliferation via overlapping transcriptomic programs shared with the RNA-binding protein HuR - Hergalant, Sébastien; Casse, Jean-Matthieu; Oussalah, Abderrahim; Houlgatte, Rémi; Helle, Déborah; Rech, Fabien; Vallar, Laurent; Guéant, Jean-Louis; Vignaud, Jean-Michel; Battaglia-Hsu, Shyue-Fang; Gauchotte, Guillaume (Frontiers in Oncology, 2023)
Meningiomas are the most common type of primary central nervous system tumors. In about 80% cases, these tumors are benign and grow very slowly, but the remainder 20% can unlock higher proliferation rates and become malignant. In this study we examined two miRs, miR-16 and miR-519, and evaluated their role in tumorigenesis and cell growth in human meningioma. In tumoral tissues, we detected decreased levels of these miRs when compared with arachnoid cells of healthy patients (miR-16: P=8.7e-04; miR-519: P=3.5e-07). When individually overexpressing these miRs in two human meningioma cell lines, Ben-Men-1 and IOMM-Lee, we observed that each showed reduced growth (P<0.001). In IOMM-Lee cells, this effect was further examined at transcriptome This is a provisional file, not the final typeset article level, where downregulated genes, among which ELAVL1/HuR (miR-16: P=6.1e-06; miR-519:P=9.38e-03), were linked to biological processes such as mitotic cell cycle regulation, prereplicative complex, and brain development (FDR<1e-05). Additionally, we uncovered a specific transcriptomic signature of miR-16/miR-519-dysregulated genes which was highly enriched in HuR targets (>6-fold; 79.6% of target genes). These results were confirmed on several public transcriptomic and microRNA datasets of human meningiomas, hinting that the putative tumor suppressor effect of these miRs is mediated, at least in part, via HuR direct or indirect inhibition.